Characterization of a Putative New Semi-Dominant Reduced Height Gene, Rht_NM9, in Wheat (Triticum aestivum L.). Issue 12 (20th December 2015) - Lu, Yuan; Xing, Liping; Xing, Shujuan; Hu, Ping; Cui, Chaofan; Zhang, Mingyi; Xiao, Jin; Wang, Haiyan; Zhang, Ruiqi; Wang, Xiue; Chen, Peidu; Cao, Aizhong
Abstract: Plant height is an important agronomic trait in cereal crops, and can affect both plant architecture and grain yield. New dwarfing genes are required for improving the genetic diversity of wheat. In this study, a novel dwarf mutant, NM9, was created by treating seeds of the wheat variety NAU9918 with ethyl methanesulfonate (EMS). NM9 showed obvious phenotypic changes, which were distinct from those caused by other dwarfing genes, especially the reduced plant height, increased effective tiller number, and elongated spike and grain length. The reduced plant height in NM9 was attributable to a semi-dominant dwarfing gene Rht_NM9, which was flanked by two closely linked SNP markers, SNP34 and SNP41, covering an 8.86-Mb region on the chromosome arm 2AS. The results of gibberellic acid (GA) sensitivity evaluation, comparative genomics analysis and allelism test indicated that Rht_NM9 was neither allelic to Rht7 and Rht21 nor homoeoallelic to Rht8, so Rht_NM9 was proposed to be a new dwarfing locus on the homoeologous group 2 chromosomes of wheat. Rht_NM9 has a negative effect on plant height and positive effects on effective tiller number and grain size, thus, Rht_NM9 could be used for elucidating the mechanisms underlying plant architecture and grain development.